2019
DOI: 10.22219/jaa.v2i2.10016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Efficacy, Motivation on Entrepreneurship, Entrepreneurship Education, and Social Environment Against Interest in Entrepreneurship on Micro, Small and Medium Enterprises Businesses in Serang Regency

Abstract: The high population growth rate in Serang Regency in the last five years which reached an average rate of 0.77% made Serang Regency one of the Regencies that contributed to the high rate of population growth in Banten Province which in the last five years reached an average lift of 2,14%. This figure is inversely proportional to the amount of adequate employment, making Serang Regency the Regency with the highest open un-employment rate in Banten Province which reached 12.78%, this causes Banten Province to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…An entrepreneur needs this motivation to grow the intention to work hard and achieve business success. Someone with a solid entrepreneurial basis will use and mobilize all their potential to succeed in entrepreneurship (Nuryanto et al 2019). The results of the study are in line with Muthalib and Yulianti (2015); Gemina et al (2016); Kisker (2016); Machmud (2017); and Budiman and Pangestu (2018), which prove that motivation affects business performance and business success.…”
Section: The Influence Of Entrepreneurial Motivation On Business Successsupporting
confidence: 79%
See 2 more Smart Citations
“…An entrepreneur needs this motivation to grow the intention to work hard and achieve business success. Someone with a solid entrepreneurial basis will use and mobilize all their potential to succeed in entrepreneurship (Nuryanto et al 2019). The results of the study are in line with Muthalib and Yulianti (2015); Gemina et al (2016); Kisker (2016); Machmud (2017); and Budiman and Pangestu (2018), which prove that motivation affects business performance and business success.…”
Section: The Influence Of Entrepreneurial Motivation On Business Successsupporting
confidence: 79%
“…The existence of solid self-motivation will encourage entrepreneurs to do the best for their business so that the business carried out has maximum results. In another study (Santoso and Oetomo 2018;and Nuryanto et al 2019) found a significant effect of self-efficacy on entrepreneurial motiva-tion. Furthermore, in another study, reason acts as a mediating influence of self-efficacy on entrepreneurial intention (Kristiadi et al 2016), and entrepreneurial achievements (Eliyana et al 2020) and entrepreneurial intention are strong predictors of one's actions to start a new business (Bernardus et al 2020).…”
Section: Entrepreneurial Motivational (Em)mentioning
confidence: 92%
See 1 more Smart Citation
“…Nilai tabel 4, menunjukkan bahwa lingkungan keluarga berpengaruh positif serta signifikan kepada niat berwirausaha. Hal ini sejalan dengan penelitian yang dilakukan Nuryanto et al, (2019) serta Agusmiati dan Wahyudin (2018) yang menyatakan adanya pengaruh lingkungan keluarga dengan niat berwirausaha.…”
Section: H4: Lingkungan Keluarga Memiliki Pengaruh Positif Dan Signif...unclassified